Treatment of purified 2,5-furandicarboxylic acid with water and heat

JP2023507469A5Active Publication Date: 2025-03-18FURANIX TECH BV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022537737
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-12-20
Filing Date
2020-12-18
Publication Date
2025-03-18
Estimated Expiration
2040-12-18

AI Technical Summary

Technical Problem

Existing methods for producing 2,5-furandicarboxylic acid (FDCA) fail to achieve sufficient purity and desirable mechanical and physical properties, leading to issues such as the presence of impurities like 5-formyl-2-furancarboxylic acid (FFCA) and monoalkyl esters, which affect polymerization reactions and handling efficiency.

Method used

A method involving hydrogenation, oxidation, recrystallization, and hydrolysis of crude FDCA, followed by a heat treatment with a treatment solvent composition exceeding 95% water, to dissolve a portion of FDCA and precipitate it at controlled temperatures, enhancing purity and mechanical properties.

Benefits of technology

The method significantly reduces impurities like FFCA and monoalkyl esters, resulting in spherical particles with improved handling and mixing properties, suitable for polymerization reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000026_0000
    Figure 00000026_0000
  • Figure 00000026_0001
    Figure 00000026_0001
  • Figure 00000026_0002
    Figure 00000026_0002
Patent Text Reader

Abstract

1. A thermal treatment of purified 2,5-furandicarboxylic acid (FDCA) to produce a carboxylic acid composition, the method comprising: providing or producing a thermal treatment composition comprising the purified carboxylic acid composition and a water-containing treatment solvent composition; subjecting the thermal treatment composition to an elevated temperature, wherein the FDCA is partially dissolved; and cooling the treated composition to separate at least a portion of the FDCA from the treated composition to obtain the carboxylic acid composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a carboxylic acid composition, each carboxylic acid composition and a starting material for the production of polyalkylene furanoate.

Background Art

[0002] It is known in the art that 2,5-furandicarboxylic acid (FDCA) is a very promising building block for replacing petroleum-based monomers in the production of high-performance polymers. In recent years, a new plant-based polyester polyethylene furanoate (PEF), a completely recyclable plastic with performance characteristics superior to those of FDCA and currently widely used petroleum-based plastics, has received much attention. These materials can significantly contribute to reducing dependence on petroleum-based polymers and plastics, while enabling more sustainable management of the earth's resources. Therefore, research has been conducted in the art to reach a technology for producing FDCA and PEF in a commercially viable manner and to enable the marketing success of these promising materials.

[0003] FDCA is typically obtained as a crude carboxylic acid composition from the oxidation of molecules having a furan moiety, such as 5-hydroxymethylfurfural (5-HMF) and the corresponding 5-HMF esters or 5-HMF ethers, and starting materials typically derived from plant-based sugars, such as by dehydration of sugars. For example, a wide variety of oxidation processes, including enzymatic or metal-catalyzed processes, are known from the prior art.

[0004] One of the most established techniques in the art uses a catalyst system containing cobalt, manganese and bromine and oxygen or air as an oxidant to oxidize a compound having a furan moiety to FDCA. Each method applicable to a wide variety of starting materials is disclosed, for example, in WO2014 / 014981A1 or WO2011 / 043660A1.

[0005] In most cases, the purity that can be obtained for crude carboxylic acid compositions by the methods described above is insufficient to achieve the required degree of purity needed for the polymerization of FDCA into PEF or other high-performance polymers. Therefore, purification methods have been developed to further purify crude carboxylic acid compositions and produce purified carboxylic acid compositions. These methods often include a comprehensive purification scheme comprising several steps for washing and isolating the obtained carboxylic acid composition, such as a hydrogenation step, a post-oxidation step, a distillation step, a recrystallization step, or similar methods. Exemplary purification methods are disclosed, for example, in WO2014 / 014981A1 or WO2016 / 195499A1.

[0006] Despite comprehensive efforts to improve existing methods for obtaining sufficiently pure FDCA (sometimes labeled as polymer-grade FDCA), the results obtained by known purification methods are often not entirely satisfactory. While prior art methods for purifying crude FDCA often yield good results for 5-formyl-2-furancarboxylic acid (FFCA), the major impurity most often obtained by incomplete oxidation of the starting materials, these methods almost always fail to achieve a significant reduction in other common impurities, some of which may be present in significant amounts depending on the oxidation process used. In particular, some prior art methods do not result in a significant reduction in the amount of 2-furancarboxylic acid (FCA), the monoacid corresponding to FDCA, which is often produced during oxidation, for example, by decarboxylation of FDCA.

[0007] Furthermore, it has been recognized in the art that solid FDCA particles obtained by prior art purification methods often possess undesirable physical and mechanical properties. These properties include, for example, an increased amount of undesirable fine powder in the solid product, i.e., very small particles often shaped like broken glass fragments, and a general decrease in the strength of the resulting particles. Other undesirable properties include, for example, aggregation, which may form during isolation and drying procedures, resulting in abnormally large particles. These properties make handling the particles significantly more difficult and expensive compared to the most common petroleum-based diacitors. For example, injecting or supplying solid FDCA products through tubes and pipes is more difficult. Moreover, the storage properties of solid FDCA are also undesirable, as the particles often tend to stick together.

[0008] Perhaps one of the most prominent drawbacks of its less-than-desirable mechanical and physical properties is that mixing solid FDCA with other starting materials and the catalyst required for polymer production can be less than ideal, resulting in a less-than-homogeneous starting mixture with concentration gradients, which can negatively impact both the required reaction time and the quality of the resulting polymer.

[0009] The inventors of this invention believe that the undesirable mechanical and physical properties are due to the particle shape and low strength, as well as the particle size distribution in the resulting purified FDCA composition. These almost always consist of plate-like particles with a large amount of fine powder. To date, no simple method for efficiently improving the mechanical and physical properties of purified FDCA is known in the art.

[0010] The aforementioned problems regarding the less-than-desirable purity and mechanical properties of solid FDCA tend to occur independently of the starting materials used in the manufacture of FDCA.

[0011] However, in recent years, a promising method for obtaining FDCA has been discovered that utilizes a significant amount of 5-HMF ether as a starting material for oxidation. As a result, the crude carboxylic acid composition obtained by such methods contains not only free diacid, i.e., FDCA, but also a significant amount of the monoalkyl ester of FDCA, and these methods now appear to be the most established methods for obtaining a significant amount of the monomethyl ester of FDCA (FDCA-Me). Each method has several advantages over equivalent methods that do not produce the monoalkyl ester of FDCA, but the aforementioned disadvantages regarding the purity and mechanical properties of the solid FDCA obtained by these methods are particularly undesirable. We have now found that the monoalkyl ester of FDCA appears to be one of the impurities that is inadequately removed by many prior art purification methods. As a result, purified FDCA compositions produced using the above techniques tend to contain significant amounts of FCA and FDCA-Me, where FCA is a potential end-terminating agent in subsequent polymerization reactions, and FDCA-Me may produce methanol, which can lead to dangerous side reactions. Furthermore, the inventors have found that even in trace amounts, the presence of FDCA-Me can result in undesirable mechanical and physical properties of solid FDCA compared to those found in purified FDCA compositions without FDCA-Me. In summary, the shortcomings of the prior art methods described above are particularly evident in methods that include FDCA-Me in crude and / or purified carboxylic acid compositions. [Prior art documents] [Patent Documents]

[0012] [Patent Document 1] WO2014 / 014981A1 [Patent Document 2] WO2011 / 043660A1 [Patent Document 3] WO2016 / 195499A1 [Patent Document 4] WO2017 / 003293A1 [Patent Document 5] WO2016195499 [Patent Document 6] WO2016195500 [Patent Document 7] WO2016 / 195500A1 [Overview of the Initiative] [Problems that the invention aims to solve]

[0013] In light of the problems described above, there has been a long-desired need to overcome the shortcomings of each of the prior art methods. An object of the present invention was to provide an improved method that further increases the purity of the resulting carboxylic acid composition, particularly with respect to FCA and / or FDCA-Me impurities. Another object was to provide a method that yields a carboxylic acid composition with good mechanical and physical properties, and thus allows for efficient handling of the solid product and favorable behavior of solid FDCA in subsequent polymerization reactions. A further object of the present invention was to provide a method that can be readily combined with existing oxidation and purification methods and can be carried out in a continuous, semi-continuous, or batch manner.

[0014] It is desirable that further process steps be carried out in a resource-efficient manner, generating only trace amounts of waste. Similarly, it is desirable to provide a method that reduces storage costs and minimizes the amount of different substances that need to be handled in the manufacturing plant, by using chemical compounds and starting materials that are also utilized in other steps of the remaining manufacturing method, such as oxidation or purification.

[0015] Similarly, it is preferable that each method requires a limited amount of energy, primarily utilizes non-corrosive materials, and can be operated in a particularly safe manner, minimizing health risks and exposure of the environment to hazardous substances. Apart from specific requirements for efficient purification of FCA and / or FDCA-Me, it is even more desirable that the method removes a wide range of possible impurities and efficiently complements prior art purification methods.

[0016] Furthermore, it was an object of the present invention to provide a carboxylic acid composition which not only has high purity but also exhibits convenient physical and / or mechanical properties that enable efficient use as a starting material in subsequent polymerization reactions.

[0017] Correspondingly, it was another object of the present invention to provide a starting material for the production of polyalkylene furanoates which allows shortening of the reaction time during polymerization and / or results in specific convenient products.

Means for Solving the Problems

[0018] The present inventors have now found a method for producing a carboxylic acid composition containing 2,5-furandicarboxylic acid, comprising: a) preparing or producing a crude carboxylic acid composition containing 2,5-furandicarboxylic acid and 5-formyl-2-furancarboxylic acid; b) purifying the crude carboxylic acid composition to produce a purified carboxylic acid composition containing 2,5-furandicarboxylic acid, which is preferably at least partly solid, more preferably at least 5% solid, and most preferably at least 80% solid, the purification comprising: - a step of hydrogenating at least a part of 5-formyl-2-furancarboxylic acid; - a step of oxidizing at least a part of 5-formyl-2-furancarboxylic acid; - a step of recrystallizing at least a part of 2,5-furandicarboxylic acid; and - a step of hydrolyzing a dialkyl ester of 2,5-furandicarboxylic acid comprising at least one step selected from the group consisting of; c) preparing or producing a treatment solvent composition containing more than 95% by mass, preferably more than 98% by mass, more preferably more than 99% by mass of water based on the mass of the treatment solvent composition; d) preparing or producing a heat treatment composition containing the purified carboxylic acid composition and the treatment solvent composition; e) A step of subjecting the heat treatment composition to a high temperature in the range of 140 to 200 °C for a time in the range of 5 to 240 minutes to obtain a treated composition, wherein the percentage of dissolved 2,5-furandicarboxylic acid with respect to the total amount of 2,5-furandicarboxylic acid is in the range of 10 to 80%, f) A step of cooling the treated composition to a temperature in the range of 20 to 80 °C and separating at least a part of 2,5-furandicarboxylic acid from the treated composition to obtain a treated mother liquor containing a carboxylic acid composition and water A method comprising the above has been found. The carboxylic acid composition that can be obtained or is obtained by the method is a modified carboxylic acid composition as compared with the crude carboxylic acid composition in step a) and the purified carboxylic acid composition in step b). The modified carboxylic acid composition is hereinafter referred to as the carboxylic acid composition.

[0019] The above method provides a further method step in the production of a carboxylic acid composition containing FDCA, which is carried out after both the oxidation step and the purification step. The further method step which is part of the present invention involves a specific heat treatment and includes mixing the purified carboxylic acid composition and the treatment solvent composition and subjecting it to the heat treatment.

[0020] During the heat treatment, a percentage of FDCA is dissolved in the treatment solvent composition while the residual FDCA remains as a solid precipitate. Without wishing to be bound by theory, it is believed that the combination of a long heat treatment results in a specific favorable particle shape, an increase in particle strength and / or a beneficial particle size distribution of solid FDCA due to the chemical equilibrium and exchange between the dissolved and precipitated FDCA. Surprisingly, it has been found that the purity of the material obtained by the method using a specific percentage of FDCA dissolved during the heat treatment is superior to the purity of the material treated by the method in which FDCA is fully dissolved.

Brief Description of the Drawings

[0021] [Figure 1]This figure shows exemplary particles of FDCA obtained by the heat-treatment-free method according to the present invention, with the scale corresponding to 100 μm. [Figure 2] This figure shows exemplary particles of FDCA obtained by the heat-treatment-free method according to the present invention, with the scale corresponding to 100 μm. [Figure 3] This figure shows exemplary particles of FDCA obtained by the heat treatment method according to the present invention, with the scale corresponding to 100 μm. [Modes for carrying out the invention]

[0022] The subject matter of the present invention is discussed in more detail below, and preferred embodiments of the present invention are disclosed. Therefore, it is particularly preferable to combine two or more preferred embodiments to obtain a particularly preferred embodiment. Accordingly, the method according to the present invention for defining two or more features of a preferred embodiment of the present invention is particularly preferred.

[0023] The carboxylic acid composition is a carboxylic acid composition that, compared to a purified carboxylic acid composition, contains a reduced amount of at least one furan-based impurity, i.e., any substance having a furan moiety other than 2,5-frandan carboxylic acid, and / or exhibits improved mechanical and / or physical properties.

[0024] Step a) of the method according to the present invention is the preparation or production of a crude carboxylic acid composition containing FDCA and FFCA, i.e., the most important impurities produced due to incomplete oxidation during the oxidation of the starting materials. According to the present invention, the crude carboxylic acid composition may be prepared, for example, obtained by another method or from separate equipment, or produced using one of several methods for obtaining a crude carboxylic acid composition containing FDCA and FFCA known from the prior art. The method of the present invention is not limited with respect to the oxidation method used to obtain the crude carboxylic acid composition. However, the crude carboxylic acid composition is preferably produced by oxidation of a compound having a furan moiety, preferably 5-hydroxymethylfurfural and / or an alkyl ether of 5-hydroxymethylfurfural, with a catalyst system containing cobalt, manganese and bromine in the presence of a solvent composition containing oxygen as an oxidizing gas, a saturated organic acid solvent having 2 to 6 carbon atoms and water.

[0025] Step b) of the method of the present invention corresponds to the purification of the crude carboxylic acid composition prepared or produced in step a), yielding a purified carboxylic acid composition containing at least partially solid 2,5-franca carboxylic acid. The method of the present invention comprises at least one purification step selected from the group defined above, these steps corresponding to the most important steps of the best established purification methods for crude carboxylic acid compositions known in the prior art. Apart from FFCA, other colorants and impurities, such as so-called heavy furanics, i.e., molecules containing one or more furan moieties, are also often removed during the purification steps.

[0026] The hydrogenation of at least a portion of 5-formyl-2-furancarboxylic acid corresponds to purification by hydrogenation based on well-known principles, in which multiple impurities in the crude carboxylic acid composition may be selectively hydrogenated and subsequently separated from FDCA.

[0027] Within the framework of the present invention, purification by hydrogenation is particularly preferred, and hydrogenation is carried out by contacting the crude carboxylic acid composition with hydrogen in the presence of a hydrogenation solvent and a hydrogenation catalyst that hydrogenates FFCA to a hydrogenation product, thereby separating FDCA from the hydrogenation product, the hydrogenation solvent being preferably water, and the hydrogenation catalyst being preferably palladium carbon. As a general principle, the hydrogenation catalyst may be selected from a wide variety of available catalysts. Typically, the hydrogenation catalyst comprises one or more metals or metal compounds selected from metals of groups 8 to 10 of the periodic table on a support. Such suitable metals include Pt, Pd, Ru, Rh, Ir, Os, Ni, Co, and mixtures thereof. As is known in the art, such hydrogenation is usually carried out under well-dissolved conditions.

[0028] The step of oxidizing at least a portion of 5-formyl-2-furancarboxylic acid corresponds to purification by post-oxidation and is based on the concept that the product of incomplete oxidation, i.e., FFCA, can be oxidized to FDCA in a subsequent oxidation reaction.

[0029] Purification of at least a portion of FDCA by recrystallization corresponds to a well-known technique of dissolving the carboxylic acid product in a second solvent and / or changing the temperature to alter the solubility of FDCA in the original solvent, thereby dissolving the desired product and subsequently precipitating it.

[0030] Finally, the step of hydrolyzing the dialkyl ester of 2,5-franjicarboxylic acid corresponds to a purification method in which the FDCA and / or monoalkyl ester of FDCA in the crude carboxylic acid composition is esterified with an alcohol to obtain the dialkyl ester of 2,5-franjicarboxylic acid (e.g., FDCA-DMe), and the purification is achieved by distillation, recrystallization, or melt crystallization of the resulting composition, and subsequently by hydrolysis of the purified dialkyl ester of FDCA to obtain purified FDCA. In other words, the step of hydrolyzing the dialkyl ester of 2,5-franjicarboxylic acid corresponds to forming the dialkyl ester of FDCA from the crude carboxylic acid composition, purifying the dialkyl ester of FDCA, and then hydrolyzing the dialkyl ester of FDCA to obtain FDCA.

[0031] In step c), a treatment solvent composition is prepared or manufactured containing more than 95% by mass of water relative to the mass of the treatment solvent composition. The treatment solvent composition is a solvent composition that acts as a solvent during the heat treatment process and as a carrier liquid in the dispersion for the remaining solid. A preferred treatment solvent composition contains a saturated organic acid having 2 to 6 carbon atoms and water.

[0032] Surprisingly, it was found that acceptable results could be obtained when the treatment solvent composition had water as its main component, i.e., contained more than 95% by mass of water relative to the mass of the treatment solvent composition. Since the use of water is relatively inexpensive and enables a highly sustainable method, it is preferable to use essentially pure water as the treatment solvent composition.

[0033] The treatment solvent composition may be obtained by mixing water and other solvents in different reactors and supplying them to the method of the present invention. However, the treatment solvent composition may also be manufactured within the framework of the method of the present invention. Here, it is particularly preferable to use the solvent composition used in purification step b) to produce the treatment solvent composition. The production of the treatment solvent composition from the solvent used in purification step b) may include all preferred steps to arrive at the treatment solvent composition as defined above, including filtration, addition of an organic acid solvent having 2 to 6 carbon atoms, addition of water, removal of the organic acid compound, or removal of water.

[0034] In a preferred embodiment, both the purified carboxylic acid composition obtained in step b) and at least a portion of the solvent used for purification in step b) are preferably sent to a heat treatment reactor, where a saturated organic acid solvent having 2 to 6 carbon atoms and / or water are added as further solvents, or removed to produce a heat-treated composition. The aforementioned portion of the solvent may consist, for example, of the solvent remaining attached to the solid after a filtration or centrifugation step.

[0035] Step d) includes preparing or producing a heat treatment composition comprising a purified carboxylic acid composition and a treatment solvent composition. The heat treatment composition actually comprises a liquid phase and a solid phase. The purified carboxylic acid composition is obtained from step b). The treatment solvent composition is from step c). The heat treatment composition may be obtained by combining the purified carboxylic acid composition and the treatment solvent composition in any way known to those skilled in the art as suitable.

[0036] In the context of the present invention, step e) is often referred to as heat treatment or heat treatment step.

[0037] According to the present invention, the heat-treated composition is subjected to a high temperature in the range of 140 to 200°C for a period of time ranging from 5 to 240 minutes. Essential to the present invention is that the percentage of dissolved FDCA relative to the total amount of FDCA is in the range of 10 to 800%. This degree of dissolution is preferably maintained for at least 5 minutes during the entire heat treatment, and the amount of each dissolved FDCA is preferably within a given range throughout the entire 5 to 240 minute heat treatment. The percentage of dissolved 2,5-franzicarboxylic acid is preferably within a given range when averaged over the duration of the heat treatment, provided that the actual value is within a predetermined range for at least 5 minutes.

[0038] Those skilled in the art can adjust the heat treatment conditions to the required degree of dissolution, and Table 1 below may be used, which lists the solubility values ​​of FDCA at a given temperature depending on the solvent composition used. These data were compiled from experimental values ​​and fitted to a suitable solubility model. Intermediate values ​​can be obtained by interpolation.

[0039] [Table 1]

[0040] After subjecting the heat-treated composition to a high temperature in heat treatment step e), the treated composition is cooled to a temperature in the range of 20 to 80°C, which reduces the solubility of FDCA in the solvent and causes precipitation of the carboxylic acid composition. The carboxylic acid composition is obtained by separating at least a portion of the solid FDCA from the treated composition, where a mother liquor containing water remains.

[0041] The carboxylic acid composition not only exhibits increased purity compared to the purified carboxylic acid composition, but also features solid particles that tend to be more spherical rather than exhibiting the undesirable plate-like shape found in the purified carboxylic acid composition. Similarly, it tends to have a more favorable particle size distribution, allowing for easier handling of the solid product. The resulting carboxylic acid composition tends to exhibit highly beneficial mixing behavior with alkylene glycols, preferably ethylene glycols, and therefore constitutes a very promising starting material for the production of polyalkylene furanoates.

[0042] The method of the present invention is not limited in terms of the technique used to obtain crude FDCA and can be combined with the most important purification methods known in the prior art. Therefore, the heat treatment step used in the method of the present invention may be usefully incorporated into existing methods for producing carboxylic acid compositions containing FDCA.

[0043] It is beneficial for the processing solvent composition to include water, as water is one of the most common solvents used in some prior art methods, for example, during hydrogenation or post-oxidation of impurities, in both oxidation reactions and the purification of crude FDCA. This allows for efficient plant management, reduces the need to store further chemicals, and therefore lowers storage costs.

[0044] Remarkably, the method of the present invention allows for obtaining the above-mentioned beneficial effects without requiring expensive catalysts or highly corrosive and / or harmful substances, and the remarkably high compatibility of water as a main component of the treatment solvent composition is particularly beneficial. Furthermore, the treatment mother liquor containing water for use in other steps of the method according to the present invention can preferably be reused in oxidation and / or purification and / or heat treatment steps. This makes it possible to achieve a particular sustainable method with less waste generation.

[0045] In step b), a method comprising at least two steps selected from the group defined in step b) is preferred. Furthermore, in step b), a method according to the present invention is preferred in which purification comprises a step of hydrogenating at least a portion of 5-formyl-2-furancarboxylic acid and a step of crystallizing at least a portion of solid 2,5-franjicarboxylic acid from the hydrogenation reaction mixture.

[0046] Within the framework of the present invention, the expression "at least a portion of" preferably means at least 20%, preferably at least 30%, more preferably at least 40%, even more preferably at least 50%, and most preferably at least 60%, and with respect to concentration, unless otherwise indicated, these values ​​are given as mass percentages.

[0047] The method according to the present invention is preferable in which the crude carboxylic acid composition and / or the purified carboxylic acid composition contains a monoalkyl ester of 2,5-franzicarboxylic acid, preferably a monomethyl ester of 2,5-franzicarboxylic acid (FDCA-Me).

[0048] As previously discussed, the preferred method is particularly beneficial because it has been found that the underlying problem of the present invention is particularly evident with respect to methods for including a monoalkyl ester of FDCA in the crude carboxylic acid composition and / or the purified carboxylic acid composition. Each crude carboxylic acid composition containing a monoalkyl ester of FDCA may be produced, for example, by oxidizing a feedstock of starting materials containing an alkyl ether of 5-HMF. Due to the fact that most of the prior art purification methods are not very suitable for completely removing the monoalkyl ester of FDCA from the crude carboxylic acid composition, it is often observed that both the crude carboxylic acid composition and the purified carboxylic acid composition contain a monoalkyl ester of 2,5-franzicarboxylic acid.

[0049] In one of the most mature technologies in this field, monomethyl and monoethyl esters of FDCA are the most important monoalkyl esters of FDCA, and here, the presence of monomethyl ester (FDCA-Me) in crude and purified carboxylic acid compositions is particularly preferred due to its high industrial importance, as monomethyl ester of FDCA is particularly prevalent. As detailed above, when purified FDCA also contains monoalkyl esters of FDCA, especially monomethyl ester of FDCA, the mechanical and physical properties of solid purified FDCA are often found to be less desirable. Without wishing to be bound by any theory, this appears to be due to the formation of so-called solid solutions of FDCA and FDCA-Me. Surprisingly, the inventors of the present invention have found that solid solutions of FDCA and FDCA-Me can be very efficiently compensated and / or prevented by the method of the present invention, which is shown to be particularly effective both for the removal of FDCA-Me and for enhancing the physical and mechanical properties of the solid product.

[0050] The method according to the present invention is preferable in which step e) is carried out in a reactor pressurized with an inert gas, preferably nitrogen or argon, and / or the heat treatment composition of step e) is stirred for at least a portion of the time, preferably by agitation, to expose the solid 2,5-flangecarboxylic acid to a shear force.

[0051] It is particularly beneficial to carry out step e) in a reactor pressurized with an inert gas, because this reduces the presence of oxygen or other reactive gaseous compounds in the reactor that may otherwise be present from the previous method steps. In these embodiments, the atmosphere in the reactor during operation consists mainly of an inert gas and a vaporized organic acid solvent and / or water. As a result, undesirable side reactions between FDCA and reactive gaseous compounds are inhibited. Therefore, the use of an inert gas enables a particularly safe method, as it reduces the possibility of potentially hazardous side reactions and / or exothermic reactions and / or fires.

[0052] While the results of the method according to the present invention are often found to be satisfactory with only the heat treatment of the heat-treated composition, the inventors have found that further stirring of the heat-treated composition in step e) and exposure of the solid FDCA particles to shear force can further increase the beneficial effects on the mechanical and physical properties of the particles of the resulting carboxylic acid composition. Without wishing to be bound by any theory, it is thought that stirring the heat-treated composition during heat treatment also enhances the homogeneity of the liquid phase, reduces the concentration gradient of impurities, and thereby promotes both purification and improvement of the mechanical properties of the resulting particles. Stirring may be achieved by any suitable means known to those skilled in the art, e.g., stirring of the heat-treated composition or the use of an external pump loop.

[0053] The method according to the present invention is preferable in which the heat treatment composition contains 2,5-franzicarboxylic acid in an amount of 15 to 45% by mass, preferably 20 to 40% by mass, relative to the mass of the heat treatment solvent composition.

[0054] Such a preferred method is beneficial because, when each amount of FDCA is used without requiring high temperatures and with high flexibility in terms of the composition of the solvent used, the desired ratio between dissolved FDCA and solid FDCA in step e) can be easily obtained.

[0055] The method according to the present invention is preferable in which the processing solvent composition contains acetic acid in an amount preferably in the range of 0.05 to 4.5% by mass, and preferably 0.1 to 3% by mass, relative to the amount of the processing solvent composition.

[0056] When the primary objective is to obtain the highest possible degree of purity and the most beneficial mechanical properties, each treatment solvent composition containing a specified amount of acetic acid is particularly preferred. It has been found that the presence of acetic acid enables the best possible removal of impurities.

[0057] As previously discussed, using water as the main component of the treatment solvent composition surprisingly yields reasonable results in the heat treatment and may be advantageous from the standpoint of cost and sustainability. In particular, heat treatment in water has been found to produce particle shapes similar to those of heat treatment in organic acids, which has been found to yield better results for impurity removal in some cases, but has other drawbacks, for example, in terms of the sustainability of the method and the cost of starting materials. Furthermore, heat treatment in water may yield similar product quality, at least in terms of FDCA-Me and FCA content, if the process parameters are adjusted (e.g., longer residence time). Without wishing to be bound by any theory, it is thought that at least part of this may be due to the conversion of FDCA-Me to FDCA by hydrolysis. Heat treatment using mainly water as the solvent, or using only water, has been found to require higher temperatures or longer residence times in some cases compared to heat treatment in organic acids. Accordingly, it is preferable that the heat treatment composition of step e) is subjected to a high temperature in the range of 160 to 200°C for a time in the range of 30 to 240 minutes.

[0058] The method according to the present invention is preferable in which the purified carboxylic acid composition produced in step b) contains less than 25% by mass, preferably less than 15% by mass, and most preferably less than 10% by mass of solvent relative to the mass of the purified carboxylic acid composition.

[0059] Each method is preferable because it may be beneficial to remove a significant amount of solvent used in the purification step b) from the purified carboxylic acid composition and then mix it with the treatment solvent composition to obtain the heat treatment composition (for example, to prevent water from the purification step from entering the solvent loop for heat treatment performed at a low water content). Each method is particularly beneficial for purification methods that utilize different solvents that may be undesirable for the heat treatment step, such as aromatic compounds, or for methods that produce a large amount of soluble by-products and / or impurities that may be removed before heat treatment by intermediate isolation of the purified carboxylic acid.

[0060] The process parameters in steps e) and f) are, - Shows a reduction in average particle size of less than 35%, preferably less than 25%, between particle size measurements at dispersion pressures of 0.2 bar and 2 bar, and / or - Having a volume-average median particle size (d50) in the range of 50 to 300 μm, preferably in the range of 60 to 200 μm. A method according to the present invention, selected to produce particles of 2,5-franzicarboxylic acid, is preferred.

[0061] One of the most beneficial aspects of the method of the present invention is that it can provide both further purification and enhancement of the mechanical and physical properties of the resulting product. Such a synergistic relationship, surprisingly, makes it possible to reliably estimate or predict either the aspect of purity or the aspect of mechanical properties by measuring and analyzing the other parameters. Since the mechanical properties and / or particle size distribution of the product obtained by the method according to the present invention can be easily determined in most cases, the preferred method is particularly advantageous because those skilled in the art can monitor the above parameters and predict with considerable certainty the time it will take to reach the desired degree of purity without having to perform a comprehensive chemical analysis of the product. Each of these advantages has been found to be particularly clear with respect to methods involving monoalkyl esters of FDCA. Without wishing to be bound by theory, this is thought to be due to the undesirable effects that, in some cases, the monoalkyl esters of FDCA have on the mechanical properties and particle size distribution of the resulting product. In other words, it has been found that the desired particle shape, as defined by the preferred method, is often achieved when the desired degree of purity for FDCA-Me is also obtained.

[0062] Both the average particle size and the volume-average median particle size (d50) are parameters well known to those skilled in the art and can be reliably determined. In fact, typical measurements used in the art to determine each parameter are expected to yield at least similar values. Therefore, in the vast majority of cases, the equipment used to determine the average particle size and the volume-average median particle size (d50) is not important. However, in case of doubt, the average particle size and the volume-average median particle size (d50) are measured using the PSD drying method with one of the most common devices for particle size measurement, namely the Malvern Panalytical laser diffraction particle size analyzer model Mastersizer 3000, with laser obscuration values ​​of 1.5% and refractive index of 1.538, and dispersion pressure of 0.2 bar.

[0063] The decrease in average particle size between particle size measurements at dispersion pressures of 0.2 bar and 2 bar is measured for the same substance, but with different aliquots (i.e., not subsequent measurements for the same particle). For this purpose, the sample is tested using two different levels of pneumatic pressure to produce particle dispersion. The results using a dispersion pressure of 0.2 bar are considered "mildest," while the results using a dispersion pressure of 2 bar represent a more vigorous dispersion. This may be used as a test of particle strength and stability under conditions that may represent, for example, the stress experienced during pneumatic conveying operations.

[0064] The method according to the present invention is preferable in which the crude carboxylic acid composition preferably contains 2-furanic acid in an amount in the range of 1 to 2000 ppm by mass relative to the mass of the composition, more preferably in an amount in the range of 1 to 1000 ppm by mass relative to the mass of the composition, and the carboxylic acid composition contains 2-furanic acid in an amount of 700 ppm by mass or less, more preferably 500 ppm by mass or less.

[0065] As discussed above, FCA is one of the impurities in crude carboxylic acid compositions containing FDCA, and these are often inadequately removed by prior art purification methods. In particular, FCA is an aromatic carboxylic acid, is somewhat stable under oxidative conditions, and is difficult to remove by oxidation. Furthermore, as an aromatic carboxylic acid, FCA is resistant to hydrogenation under conditions that hydrogenate FDCA but not FDCA, and is difficult to remove by hydrogenation. Alternatively, FDCA can be esterified to form a diester, and FCA can be removed by subsequent distillation, recrystallization, or melt crystallization, but this method is also not suitable for FCA removal because new FCA is formed when the purified dialkyl ester is hydrolyzed to produce a diacid. Surprisingly, it has been found that the method of the present invention, namely the method including heat treatment, can significantly reduce the amount of FCA in the carboxylic acid composition. The preferred method is particularly advantageous due to its remarkably high suitability for the removal of FCA from carboxylic acid compositions containing FDCA. As previously discussed regarding mechanical and physical properties, it has been found that, surprisingly, with regard to carboxylic acid compositions containing FCA, the possibility of satisfactory mechanical and physical properties of the product can be estimated or predicted with considerable certainty from the concentration of FCA in the carboxylic acid composition, using heat treatment. It has been found that carboxylic acid compositions containing FCA in an amount of 700 ppm by mass or less, preferably 500 ppm by mass or less, relative to the mass of the carboxylic acid composition, exhibit satisfactory physical and mechanical properties after heat treatment. This is beneficial because, depending on the availability of equipment in the facility, it may be preferable to analyze the chemical composition rather than directly analyzing the mechanical properties of the obtained product.

[0066] The crude carboxylic acid composition contains 2,5-franzicarboxylic acid in an amount ranging from 90 to 99.5% by mass, preferably in an amount ranging from 94 to 99% by mass, relative to the mass of the crude carboxylic acid composition. and / or The crude carboxylic acid composition contains 2,5-francicarboxylic acid in an amount ranging from 90 to 99.5% by mass, preferably in the range of 94 to 99% by mass, relative to the total mass of all franci in the crude carboxylic acid composition. and / or The crude carboxylic acid composition contains 5-formyl-2-furanic acid in an amount ranging from 100 to 3800 ppm by mass, preferably in the range of 150 to 3000 ppm by mass, and more preferably 1500 ppm or less by mass, relative to the mass of the crude carboxylic acid composition. and / or A preferred method involves the crude carboxylic acid composition containing a monoalkyl ester of 2,5-franzicarboxylic acid in an amount ranging from 0.2 to 50% by mass, preferably 0.3 to 3% by mass, relative to the mass of the crude carboxylic acid composition.

[0067] The above method is preferred because it has been found that the heat treatment performed in such a manner is particularly effective when used in the method starting with each crude carboxylic acid composition. The term furanics is known in the art and describes all compounds containing at least one furan moiety, i.e., a substituted or unsubstituted furan ring. In fact, the most important furanics are typically furan, 5-HMF and its ethers and esters, FCA and its esters, FDCA and its esters, FFCA and its esters, 2,5-diformylfuran, 5-methylfuran-2-carboxylic acid, and dimers of these compounds.

[0068] The purification in step b) includes a step of hydrogenating at least a portion of 5-formyl-2-furancarboxylic acid, and / or A preferred method according to the present invention includes a step of isolating the purified carboxylic acid composition in step b), wherein the isolation includes filtration and / or washing and / or drying.

[0069] Heat treatment is preferred over hydrogenation as a purification method, as it has been found to yield particularly good results when combined with hydrogenation. Purification by hydrogenation is particularly cost-effective and suitable not only for large volumes of products handled in continuous or semi-continuous methods, but also for the removal of FFCA from crude carboxylic acid compositions. Hydrogenation as a purification method is also particularly preferred because this method typically utilizes a hydrogenation solvent mainly consisting of water. Therefore, the hydrogenation solvent composition can often be used as a precursor to the treatment solvent composition used during heat treatment. In most cases, it is necessary to add water and / or organic acids to adjust the desired composition of the treatment solvent composition, but in some cases, at least a portion of the hydrogenation solvent can be used directly as the treatment solvent composition without modification. However, in these cases, it is often preferable to remove at least a portion of the hydrogenation solvent in order to establish the desired percentage of dissolved FDCA during heat treatment. For example, a hydrogenation process utilizing well-dissolved conditions can then be crystallized using an evaporative crystallizer to remove a portion of the hydrogenation solvent and increase the concentration of FDCA in the process. Other options for partial solvent removal include methods such as decantation, hydrocyclone, or purification.

[0070] While the methods of the present invention reliably yield good results with respect to the purity and mechanical properties of carboxylic acid compositions, it has been found that it may be particularly beneficial to include an isolation step in which the purified carboxylic acid composition is isolated from other components, such as the solvent used for purification. Such an isolation step typically includes filtration and / or washing and / or drying steps. Although each method is not typically optimized in terms of cost and / or time efficiency, the intermediate isolation of the solid product facilitates purification during heat treatment and allows for tight control of the composition of the heat-treated composition without the need to consider changes in the liquid components. Accordingly and as described above, each method is expected to yield one of the highest purities of the carboxylic acid composition.

[0071] The purified carboxylic acid composition contains 2,5-franjic acid in an amount ranging from 95 to 99.9% by mass, preferably in an amount ranging from 98 to 99.9% by mass, relative to the mass of the purified carboxylic acid composition. and / or The purified carboxylic acid composition contains 5-formyl-2-furanic acid in an amount ranging from 1 to 200 ppm by mass, preferably in an amount ranging from 1 to 100 ppm by mass, relative to the mass of the purified carboxylic acid composition. and / or The purified carboxylic acid composition contains a monoalkyl ester of 2,5-franzicarboxylic acid in an amount ranging from 100 to 13,000 ppm by mass, preferably in the range of 200 to 11,000 ppm by mass, relative to the mass of the purified carboxylic acid composition. and / or The method according to the present invention is preferred, wherein the purified carboxylic acid composition contains 2-furanic acid in an amount in the range of 1 to 2500 ppm by mass, preferably in the range of 1 to 1700 ppm by mass, relative to the mass of the purified carboxylic acid composition.

[0072] Each method is preferred because the heat treatment of the present invention has been found to work particularly well with purified carboxylic acid compositions of a given standard. The methods of the present invention tend to result in an increase in the degree of purity of the product, as well as enhancement of its mechanical and physical properties, for a wide range of purified carboxylic acid compositions studied. However, in some cases, a decrease in efficiency was observed when the overall amount of impurities, particularly the amounts of FDCA and alkyl esters of FCA, exceeded a certain threshold. Similar effects have been observed in other purification methods due to the fact that the amount of solvent that may be used to dissolve impurities is limited by the inherent characteristics of the heat treatment, namely the need for a certain amount of FDCA to remain in the solid phase during the heat treatment.

[0073] Similarly, the above method is preferred because the heat treatment of the present invention has been found to be less suitable for removing FFCA, which is also an undesirable end-terminating agent in polymer-grade FDCA. Accordingly, it is preferred that the purification step b) is carried out so as to remove most of the FFCA before the heat treatment. Understanding that the ability of heat treatment to remove FFCA is relatively low, those skilled in the art can easily adapt the prior art method to yield a purified carboxylic acid composition having a desired amount of FFCA.

[0074] The temperature in step e) is in the range of 150 to 190°C, preferably in the range of 160 to 190°C. and / or The heat treatment composition in step e) is subjected to a time range of 15 to 120 minutes, preferably 30 to 90 minutes, most preferably 0.7 * (220-T / ℃)~3.0 * The temperature is high for a period of time within the range of (220-T / ℃), where T is the temperature in step e). and / or In step e), it is preferable that the percentage of dissolved 2,5-franglicarboxylic acid relative to the total amount of 2,5-franglicarboxylic acid is in the range of 20 to 60%, preferably in the range of 30 to 60%.

[0075] The above method is preferred because it defines process parameters for heat treatment that have been found to be most suitable for obtaining the best results for the carboxylic acid composition in terms of both purity and mechanical properties. Here, the temperature range during heat treatment and the percentage of dissolved FDCA are related to factors that are mainly determined by the composition and amount of the treatment solvent composition. Conveniently, a suitable residence time may be given based on screening experiments, depending on the heat treatment temperature disclosed above.

[0076] The composition processed in step f) is cooled to a temperature in the range of 30 to 80°C, preferably in the range of 40 to 80°C. and / or Step f) includes a step of treating the treatment mother liquor and removing at least a portion of the water from the remaining treated composition, and / or A preferred method according to the present invention includes step f) a step of reusing at least a portion of the processing mother liquor to provide the processing solvent composition for step c).

[0077] It may be understood that the cooling in step f) is expected to affect the mechanical properties of the resulting product, as a decrease in temperature can reduce the solubility of FDCA in the treatment solvent composition and may lead to precipitation of dissolved FDCA. Accordingly, those skilled in the art who wish to modify the mechanical properties of the carboxylic acid composition should attempt to vary the temperature gradient between the heat treatment in step e) and the cooling in step f). It has been found that it can be beneficial if the temperature gradient in step f) is reproducibly controlled and not too steep. It is preferable to cool the treated composition to a temperature well above typical room temperature of 20-25°C. A cooling rate of 2530-120K / hour is preferred, with a maximum cooling rate of 600K / hour being extremely acceptable. While we do not wish to be constrained by theory, we believe that the presence of a large solid fraction at the processing temperature reduces the risk of powder formation or spontaneous nucleation, which may otherwise be experienced at these relatively high cooling rates. High cooling rates are advantageous because the thermal stress on the system is not prolonged beyond the stress required to produce the desired treatment effect. Excessive thermal stress can lead to undesirable reactions, such as color formation. A high cooling rate is advantageously achieved by evaporating at least a portion of the solvent, for example, by boiling the solvent.

[0078] To increase the sustainability of the heat treatment process and to reduce the amount of waste generated by the method according to the present invention, it is preferable to reuse at least a portion of the treatment mother liquor and return it to the heat treatment process. This means that at least a portion of the treatment mother liquor is used as the treatment solvent composition in the heat treatment of the purified carboxylic acid composition. In this reuse process, it may be important to adjust the solvent composition for any changes that have occurred. For example, if the purified carboxylic acid composition is wet with water, e.g., filtered and washed but not dried, the water should be incorporated into the mother liquor after heat treatment and at least a portion removed from the mother liquor before reuse. In this way, the overall heat-treated composition can be maintained at a desired concentration level.

[0079] Furthermore, the present invention relates to a carboxylic acid composition comprising 2,5-franzicarboxylic acid in an amount greater than 98% by mass relative to the mass of the carboxylic acid composition, wherein the carboxylic acid composition particles exhibit a decrease in average particle diameter of less than 35% between particle size measurements at dispersion pressures of 0.2 bar and 2 bar, the carboxylic acid composition preferably comprises less than 0.1% by mass of a saturated organic acid solvent having 2 to 6 carbon atoms, and the carboxylic acid composition is preferably produced using the method of the present invention.

[0080] Faced with the objective of providing a carboxylic acid composition having good physical and / or mechanical properties and that can be efficiently processed, for example, during storage or transport of the product, the inventors have surprisingly found that the technical problem can be solved by providing the above-mentioned carboxylic acid composition. Each parameter is an indicator that the particles are suitable and therefore beneficial for efficient handling and long-term storage.

[0081] The carboxylic acid composition of the present invention may be produced using the method of the present invention, particularly by a heat treatment step of a purified carboxylic acid composition. Accordingly, a carboxylic acid composition produced using the method of the present invention or a preferred embodiment of the method of the present invention is preferred.

[0082] The carboxylic acid composition particles have a volume-average median particle size (d50) in the range of 50 to 300 μm, preferably in the range of 60 to 200 μm. and / or The carboxylic acid composition particles have a d10 of 20 μm or more, where d10 is defined as the diameter of 10 volume percent of the particles having a smaller diameter. and / or The carboxylic acid composition particles have a d90 of 400 μm or less, where d90 is defined as the diameter of 90% by volume of particles having a smaller diameter. and / or A carboxylic acid composition according to the present invention is preferred in which the ratio of d50 to d10 is in the range of 1 to 3, preferably in the range of 1.5 to 2.5.

[0083] Analysis of these carboxylic acid composition particles, which exhibited the most beneficial mechanical properties, revealed that each carboxylic acid composition particle tended to exhibit a specific particle size distribution that is considered to contribute at least to the fact that the carboxylic acid composition particles according to the present invention can be easily injected and pumped through piping, while simultaneously maintaining their properties even after long-term storage. Furthermore, these carboxylic acid composition particles were found to possess properties advantageous for producing slurries with good stability and good pumping and mixing characteristics.

[0084] The carboxylic acid composition contains a monoalkyl ester of 2,5-franzicarboxylic acid, preferably a monomethyl ester of 2,5-franzicarboxylic acid, in an amount ranging from 200 to 5000 ppm by mass relative to the mass of the carboxylic acid composition. and / or The carboxylic acid composition contains 2-furanic acid in an amount ranging from 10 to 500 ppm by mass, preferably 20 to 200 ppm by mass, relative to the carboxylic acid composition. and / or A carboxylic acid composition according to the present invention is preferred in which the carboxylic acid composition contains 5-formyl-2-furancarboxylic acid in an amount ranging from 1 to 100 ppm by mass, preferably 2 to 50 ppm by mass, and most preferably less than 30 ppm by mass, relative to the carboxylic acid composition. Such a carboxylic acid composition is preferred not only because the mechanical parameters are particularly favorable, but also because the composition further contains small amounts of impurities known to have the most detrimental effect on the polymerization behavior of the carboxylic acid composition.

[0085] The present invention also relates to a starting material for the production of a polyalkylene furanoate, also called poly(alkylene-2,5-flangecarboxylate), comprising a carboxylic acid composition according to the present invention, an alkylene glycol, preferably ethylene glycol, and a polymerization catalyst, wherein the polyalkylene furanoate is preferably poly(ethylene-2,5-flangecarboxylate).

[0086] Each starting material for the production of polyalkylene furanoates is a mixture of the carboxylic acid composition of the present invention, alkylene glycol, and a typical polymerization catalyst known in the art. Each composition is particularly suitable for use in polymerization reactions yielding polyalkylene furanoates. As discussed above, this is due to the beneficial mechanical and physical properties of the carboxylic acid composition of the present invention, i.e., the carboxylic acid composition obtained by the method of the present invention. The shape of the FDCA particles and a particular particle size distribution tend to allow for very efficient mixing with alkylene glycol, even at low molar ratios. In clear contrast, solid FDCA obtained by prior art purification methods is often found not to form the desired mixture with ethylene glycol, even at low molar ratios. This imposes a significant problem on polymerization methods that cannot be easily adapted to yield a high-performance polymer of a given composition and thus simply increase the molar ratio, allowing for enhanced mixing of the starting materials, or providing the additional energy required to remove undesirable excess glycol. As a result, the use of the carboxylic acid composition of the present invention and its use as a starting material in the polymerization of polyalkylene furanoates is highly beneficial compared to purified carboxylic acid compositions containing monoalkyl esters of FDCA, particularly due to their manufacturing history, and fulfills a long-desired need.

[0087] The present invention will be described in more detail below using experiments.

[0088] (Example A) Heat treatment: Preparation of A1-Purified FDCA A crude carboxylic acid composition (cFDCA) containing 2,5-franzicarboxylic acid and 5-formyl-2-furancarboxylic acid was prepared as previously described in accordance with the teachings of WO2017 / 003293A1. This cFDCA was then purified by hydrogenation according to the teachings of WO2016195499 and WO2016195500 to produce purified FDCA, denoted as hFDCA (representing hydrogenated FDCA). To understand the results, it is convenient to analyze the actual composition of hFDCA.

[0089] Analysis of hFDCA revealed that it contained over 98% by mass of 2,5-franzicarboxylic acid (FDCA), with the main impurities being the monomethyl ester of 2,5-franzicarboxylic acid (FDCA-Me) at 10,300 ppm by mass and 2-furancarboxylic acid (FCA) at 1,680 ppm by mass. These levels of impurities are generally considered unsuitable for use in polymer manufacturing. In particular, the monoester of FDCA generates methanol during polymer manufacturing, which is undesirable. The monocarboxylic acid, FCA, has only one polymerization site and acts as a end-terminating agent, limiting molecular weight growth. Furthermore, FCA is also involved in color formation.

[0090] A2 - Experimental equipment for heat treatment Heat treatment tests were conducted using a laboratory autoclave. Heating and cooling were performed through the autoclave walls, and a stirrer was used.

[0091] A3-Comparative Examples 1 and 2-Dissolution of FDCA Comparative Examples 1 and 2 used 10 wt% hFDCA in water, which was heated to 160°C during the heat treatment to fully dissolve the FDCA (a small amount of hFDCA is required to allow complete dissolution). This complete dissolution is not according to the present invention. The heat-treated compositions were then held at a given temperature for 30 minutes. In Comparative Example 1, the sample was then cooled to 40°C by rapid cooling. In Comparative Example 2, the sample was first cooled to 109°C over 15 minutes by evaporating water using reduced pressure, and then cooled to 40°C by rapid cooling. In each case, the sample was then filtered at 40°C under vacuum, washed with water (1:1 by mass compared to the dry solid), and then dried.

[0092] As shown in the table below, the treatment resulted in a reasonable reduction in the monoester content of the dried FDCA, but the FCA content actually increased compared to the initial feed (indicating further decarboxylation of FDCA / FDCA-Me when processed in water).

[0093] Microscopic images clearly showed that the particles obtained after heat treatment had a "broken glass" appearance with somewhat flat plates and sharp edges, and contained a significant level of fine powder. This particle shape is considered undesirable. Exemplary photographs of the particles obtained in Comparative Example 1 and Comparative Example 2 are shown in Figures 1 and 2, respectively. The photographs were obtained using a Euromex iScope IS.1053-PLPOLRi microscope at a magnification of 20x.

[0094] [Table 2]

[0095] A4-Comparative Examples 3 and 4-Temperature Comparative Examples 3 and 4 were prepared in the same manner as described above for Comparative Examples 1 and 2, and the process parameters are summarized in Table 2 (Table 3) below. In both cases, the heating rate was 1.5 K / min until the process temperature (i.e., lower than that defined in the present invention) was reached, the process temperature was maintained for 1 hour, and then cooled to 40°C at 1 K / min.

[0096] To facilitate understanding, the estimated solubility of FDCA in a given solvent at the process temperature is also presented.

[0097] As shown in Table 2 (Table 3) below, heat treatment by incomplete dissolution at lower temperatures resulted in a reasonable reduction in both the monoester and FCA content of the dry FDCA. However, when Comparative Example 4 was compared with Comparative Examples 1 and 2, the removal efficiency for FCA increased, but the removal efficiency for FDCA-Me decreased.

[0098] Microscopic images clearly showed that the particles obtained after heat treatment had sharp edges and a plate-like appearance. This particle shape is considered undesirable.

[0099] [Table 3]

[0100] A5-Examples 1, 2 and 3 Examples 1, 2, and 3 were prepared in the same manner as described above for Comparative Examples 1 and 2, and the process parameters are summarized in Table 3 (Table 4) below. In all cases, the heating rate was 1.5 K / min until the process temperature was reached, the process temperature was maintained for 1 hour, and then cooled to 40°C. In Examples 1 and 3, cooling was performed at a rate of 1 K / min. In Example 2, the sample was first cooled to 107°C in 7 minutes by evaporating water using reduced pressure, and then cooled to 40°C at a rate of 1 K / min.

[0101] To facilitate understanding, the estimated solubility of FDCA in a given solvent at the process temperature is also presented.

[0102] Examples 1 and 2 are not considered to be part of the present invention and are included for comparative purposes only.

[0103] As shown in Table 3 (Table 4) below for Example 3, the heat treatment according to the present invention results in a significantly greater reduction in both the FDCA-Me content and FCA content of the dry FDCA compared to Comparative Examples 1-4, demonstrating that both temperature and the precise degree of FDCA dissolution are important.

[0104] Furthermore, microscopic images clearly showed that the particles obtained after heat treatment had a somewhat smooth and rounded shape and contained a low level of fine particles. This particle shape is considered very favorable. An exemplary photograph of the particles obtained in Example 3 is shown in Figure 3. The photograph was obtained using a Euromex iScope IS.1053-PLPOLRi microscope at a magnification of 20x.

[0105] [Table 4]

[0106] (Example B) particle B1 - Preparation of different FDCA feeds for use in heat treatment A mixed furnicus mainly containing 5-methoxymethylfurfural (5-HMF ether) and 5-hydroxymethylfurfural (5-HMF) was prepared according to the teachings of WO2017 / 003293A1 by acid-catalyzed dehydration of fructose in methanol, followed by partial neutralization of the acid, and recovery of 5-methoxymethylfurfural and 5-hydroxymethylfurfural.

[0107] After recovery, the mixed franix was supplied to an oxidation reactor with a catalyst containing acetic acid (HAc) and sources of cobalt, manganese, and ionic bromine, in accordance with the teachings of WO2011 / 043660A1. The oxidation products were mainly 2,5-franzicarboxylic acid and monomethyl esters of 2,5-franzicarboxylic acid, with smaller amounts of 5-formyl-franzicarboxylic acid and trace amounts of other by-products. This corresponds to the crude carboxylic acid composition hereafter referred to as cFDCA. It should be noted that the use of crude cFDCA allows for a particularly good analysis of the effects of the heat treatment of the present invention, as cFDCA contains the largest amount of impurities and the observed effects are particularly evident. Therefore, although cFDCA was not subjected to the purification step defined in the method of the present invention, the results obtained below using cFDCA are very important for evaluating the effects of the method of the present invention.

[0108] The crude carboxylic acid composition was further purified by various methods.

[0109] In one purification method, the diacid was esterified with methanol to form a dimethyl ester of 2,5-franzicarboxylic acid. This ester was then purified, hydrolyzed in the presence of a base, and acidified again to form a purified carboxylic acid composition. The corresponding sample is denoted as eFDCA.

[0110] In another purification method, following the instructions in WO2016 / 195499A1 and WO2016 / 195500A1, the crude carboxylic acid composition was mixed with water and hydrogen, heated to dissolve the solid, and then hydrogenated in a flow system in the presence of a catalyst to form a purified carboxylic acid composition. The corresponding sample is denoted as hFDCA.

[0111] Finally, a feed of another FDCA was obtained from hydrogenated FDCA (hFDCA), which was thoroughly dissolved and then recrystallized from water. The corresponding sample is denoted as rFDCA.

[0112] Analysis of these supplies revealed that they contained the levels of FDCA-Me and FCA shown in the table below (ranges indicate the results of multiple measurements on the same type of sample).

[0113] [Table 5]

[0114] B2-Particle size analysis As described above, FDCA samples prepared by various methods were subjected to particle size analysis to determine the particle size distribution (PSD) of the samples. Particle size analysis was performed using a Malvern Panalytical laser diffraction particle size analyzer, model Mastersizer 3000. The instrument was used to generate a complete particle size distribution, which was then incorporated into a summary table along with the well-established d10, d50, and d90 parameters, representing the volume-average particle size (diameter) cutoffs for 10%, 50%, and 90% of the sample volume. Furthermore, statistics representing the width of the particle size distribution, reported as the ratio d50 / d10, are presented. Large values ​​of this ratio indicate a distribution with a significant population of particles much smaller than the median, or of fine particles, which was found undesirable.

[0115] B3 - Stress Test In addition to standard particle size analysis, samples were tested using multiple levels of pneumatic pressure to create particle dispersion. Results using a dispersion pressure of 0.2 bar were considered "mild," while results using a dispersion pressure of 2 bar indicated a more aggressive dispersion. This may be used as a test of particle strength and stability under conditions that may represent, for example, the stress experienced during pneumatic conveying operations. This test is quantitatively shown in the table below as a reduction in d50 when tested at 2.0 bar compared to 0.2 bar.

[0116] B4 - Experimental equipment for heat treatment A 5-liter autoclave made from 316L stainless steel was used for heat treatment and corresponding crystallization. The system is at its rated pressure to accommodate the selected temperature and solvent. The vessel is made from 316L stainless steel. Temperature, pressure, and shaft speed are recorded. The impeller is an Ekato "Viscoprop," which is suitable for this purpose.

[0117] B5-Comparative Examples 5~12-Particle size distribution In Comparative Examples 5-12, each material was fully dissolved during heat treatment, and then cooled and crystallized according to the details in the table below. In each case, the material was held at the heat treatment temperature for 30 minutes, and then cooled to 40°C. Comparative Example 7 used a more sophisticated cooling scheme with cooling rates of 20K / hour from 180°C to 140°C, then 40K / hour from 140°C to 100°C, and then 60K / hour from 100°C to 40°C.

[0118] The obtained particles were analyzed to determine the particle size distribution. The d50 / d10 ratio was used as a measure of the distribution width, with larger numbers indicating a significant fraction of particles with diameters much smaller than the median.

[0119] [Table 6]

[0120] B6-Examples 4-9-Particle Size Distribution The heat treatments for Examples 4-9 were carried out in the same manner as described above for Comparative Examples 5-12, and the process parameters are summarized in Table 6 (Table 7) below. In Examples 8 and 9, the heat treatment time was extended to 240 minutes.

[0121] [Table 7]

[0122] Examples 4-9 use lower water concentrations in the treatment solvent composition and are not in accordance with the present invention. However, the inventors found the above trend even with treatment solvent compositions containing more than 95% by mass of water. Therefore, from the data obtained, it can be inferred that the heat treatment according to the present invention results in a much more favorable particle size distribution, accompanied by a significant reduction in fine particles, indicated by a decrease in the d50 / d10 ratio.

[0123] B7-Comparative Examples 13 and 14-Particle Strength Comparative Examples 13 and 14 were prepared by obtaining hydrogenation-purified FDCA (hFDCA) samples according to the conditions in the following table (Table 8), and subjecting them to heat treatment by sufficient dissolution and controlled crystallization. In each case, the sample was 20 wt% FDCA in water, heated to 180°C to sufficiently dissolve the hFDCA, and then cooled to 40°C.

[0124] These samples were tested to generate particle size distributions at dispersion pressures of 0.2 bar and 2.0 bar, and the particle strength was tested. The results are shown in Table 7 (Table 8) below.

[0125] [Table 8]

[0126] B8 - Examples 10-12 - Particle Strength: Examples 10-12 involved obtaining hydrogenation-purified FDCA (hFDCA) samples according to the conditions in the table below, and subjecting them to heat treatment by partial dissolution and controlled crystallization. In each case, the sample was maintained at the desired temperature for a specified time and then cooled to 40°C.

[0127] These samples were tested to generate particle size distributions at dispersion pressures of 0.2 bar and 2.0 bar, and the particle strength was tested. The results are shown in Table 8 (Table 9) below.

[0128] [Table 9]

[0129] Examples 10-12 use lower water concentrations in the treatment solvent composition and therefore do not conform to the present invention. However, the inventors also found the above trend for treatment solvent compositions containing more than 95% by mass of water. Therefore, from the data obtained, it can be inferred that the heat treatment according to the present invention yields much more stable particles after heat treatment, as indicated by the reduced percentage reduction in d50 when comparing the 2.0 bar test with the 0.2 bar dispersion pressure test.

[0130] (Experiment C) heat treatment Purified FDCA was prepared by hydrogenation of crude FDCA in water, followed by crystallization, cooling, filtration, and washing with water. The solvent composition was prepared from acetic acid and water in a ratio of 65:35 by mass. For each experiment, 30 grams of FDCA was mixed with 70 grams of solvent. The mixture was heated to the desired temperature in an autoclave and held at constant temperature for 60 minutes with stirring. The mixture was then rapidly cooled to 40°C and subsequently filtered. The filtered cake was washed with solvent, dried, and analyzed for the listed impurities. The results are shown in the table below. The estimated percentage of total FDCA dissolved at the heat treatment temperature is also shown. The 40°C run is for comparison only and is not in accordance with the present invention.

[0131] [Table 10]

[0132] Examples 13-15 use lower water concentrations in the treatment solvent composition and therefore do not conform to the present invention. However, the inventors also found the above trend for treatment solvent compositions containing more than 95% by mass of water. Therefore, from the data obtained, it can be inferred that in the heat treatment according to the present invention, temperature and degree of dissolution are important for the product obtained by the heat treatment, which is measured as the relative removal of FDCA-Me and FCA, respectively.

[0133] (Experiment D) Solvent composition FDCA was prepared by hydrogenation in water, followed by crystallization, cooling, filtration, and washing with water. Solvent compositions were prepared from acetic acid and water in different mass ratios shown in the table. For each experiment, a composition containing 27–30 wt% FDCA was prepared in the desired solvent. The mixture was heated to 180°C in an autoclave and held at constant temperature for 60 minutes with stirring. The mixture was then rapidly cooled to 40°C and subsequently filtered. The filtered cake was washed with solvent, dried, and analyzed for reported impurities. The results are shown in Table 10 (Table 9) below. The estimated percentage of total FDCA dissolved at the heat treatment temperature (180°C) is also reported.

[0134] [Table 11]

[0135] Examples 16-20 use lower water concentrations in the treatment solvent composition and therefore do not conform to the present invention. However, the inventors found the above trend even for treatment solvent compositions containing more than 95% by mass of water. Therefore, from the data obtained, it can be estimated that the heat treatment according to the present invention can achieve excellent removal rates of FDCA-Me and FCA for a wide range of solvent compositions.

[0136] (Experiment E) Crystallization from water after complete dissolution Further comparative experiments were performed upon complete dissolution. Mixtures of FDCA were prepared by mixing different purified FDCA compositions, generating samples with variations in FCA and FDCA-Me relative to FDCA. Samples were prepared at a total concentration of 4 wt% FDCA to achieve sufficient dissolution at 140°C. After treatment in water, the samples were cooled to crystallize the FDCA, and the cake was analyzed for purity. The table below shows the results upon recrystallization from water.

[0137] [Table 12]

[0138] The data shows a significant improvement in FCA removal efficiency when only a limited amount of FDCA-Me is present. Furthermore, it is observed that FDCA-Me is not removed by recrystallization from water under these conditions, but is virtually completely reintegrated into the cake. Comparative experiment 20 approximates the FDCA-Me concentrations encountered in actual operations and shows the often insufficient removal efficiency.

Claims

1. A method for producing a carboxylic acid composition comprising 2,5-furandicarboxylic acid, comprising the steps of: a) providing or producing a crude carboxylic acid composition comprising 2,5-furandicarboxylic acid and 5-formyl-2-furancarboxylic acid; b) purifying the crude carboxylic acid composition to produce a purified carboxylic acid composition comprising 2,5-furandicarboxylic acid, the purification comprising: - hydrogenating at least a portion of the 5-formyl-2-furancarboxylic acid; - oxidizing at least a portion of the 5-formyl-2-furancarboxylic acid; - recrystallizing at least a portion of the 2,5-furandicarboxylic acid; and - hydrolyzing the dialkyl ester of 2,5-furandicarboxylic acid and at least one step selected from the group consisting of: c) providing or manufacturing a processing solvent composition comprising greater than 95% water by weight based on the weight of the processing solvent composition; d) providing or manufacturing a thermal treatment composition comprising a purified carboxylic acid composition and a treatment solvent composition; e) subjecting the heat-treated composition to an elevated temperature ranging from 140 to 200° C. for a time ranging from 5 to 240 minutes to obtain a treated composition, the percentage of dissolved 2,5-furandicarboxylic acid relative to the total amount of 2,5-furandicarboxylic acid being in the range of 10 to 80%; f) cooling the treated composition to a temperature in the range of 20 to 80° C. and separating at least a portion of the 2,5-furandicarboxylic acid from the treated composition to obtain a treated mother liquor comprising a carboxylic acid composition and water. A method comprising:

2. 2. The method of claim 1 , wherein the crude carboxylic acid composition and / or the purified carboxylic acid composition comprises the monomethyl ester of 2,5-furandicarboxylic acid.

3. Step e) is carried out in a reactor pressurized with an inert gas, and / or 3. The method of claim 1 or 2, wherein the heat-treated composition of step e) is agitated at least a portion of the time to expose the solid 2,5-furandicarboxylic acid to shear forces.

4. the heat treatment composition comprises 2,5-furandicarboxylic acid in an amount of 15 to 45% by weight, based on the weight of the heat treatment composition; and / or The processing solvent composition comprises acetic acid and water.

4. The method according to any one of claims 1 to 3.

5. The process parameters in steps e) and f) are - exhibits a reduction in mean particle size of less than 35% between particle size measurements at dispersion pressures of 0.2 bar and 2 bar; and / or - having a volume average median particle size (d50) in the range of 50 to 300 μm, 5. The method of claim 1 , selected to produce particles of 2,5-furandicarboxylic acid.

6. 6. The process according to any one of claims 1 to 5, wherein the crude carboxylic acid composition comprises 2-furan carboxylic acid in an amount in the range of 1 to 2000 ppm by weight, based on the weight of the composition, and the carboxylic acid composition comprises 2-furan carboxylic acid in an amount of 700 ppm by weight or less.

7. 7. The process of claim 1, wherein the crude carboxylic acid composition comprises the monoalkyl ester of 2,5-furandicarboxylic acid in an amount ranging from 0.2 to 5.0 weight percent, based on the weight of the crude carboxylic acid composition.

8. 8. The process according to claim 1, wherein the purification in step b) comprises hydrogenating at least a portion of the 5-formyl-2-furancarboxylic acid.

9. 9. The method according to claim 1, wherein in step e), the percentage of dissolved 2,5-furandicarboxylic acid relative to the total amount of 2,5-furandicarboxylic acid is in the range of 20 to 60%.

10. the temperature of step e) is in the range of 150 to 190° C., and / or 10. The method according to any one of claims 1 to 9, wherein the heat treatment composition of step e) is subjected to elevated temperature for a time in the range of from 15 to 120 minutes.

11. 11. The method according to any one of claims 1 to 10, wherein the treated composition of step f) is cooled to a temperature in the range of 30 to 80°C.

12. A carboxylic acid composition produced by the method according to any one of claims 1 to 11, comprising:

1. A carboxylic acid composition comprising greater than 98% by weight of 2,5-furandicarboxylic acid, wherein the carboxylic acid composition particles exhibit less than a 35% decrease in average particle size between particle size measurements at dispersion pressures of 0.2 bar and 2 bar, and the carboxylic acid composition comprises less than 0.1% by weight of a saturated organic acid solvent having 2 to 6 carbon atoms.

13. the carboxylic composition particles have a volume average median particle size (d50) in the range of 50 to 300 μm; and / or The ratio of d50 to d10 is in the range of 1 to 3. The carboxylic composition of claim 12.

14. the carboxylic acid composition comprises the monomethyl ester of 2,5-furandicarboxylic acid in an amount ranging from 200 to 5000 ppm by weight, based on the weight of the carboxylic acid composition; and / or the carboxylic acid composition comprises 2-furan carboxylic acid in an amount ranging from 10 to 500 ppm by weight based on the carboxylic acid composition; 14. A carboxylic acid composition according to claim 12 or 13.